Risk factors for infections in myelofibrosis: role of disease status and treatment. A multicenter study of 507 patients. Issue 1 (12th November 2016) - Polverelli, Nicola; Breccia, Massimo; Benevolo, Giulia; Martino, Bruno; Tieghi, Alessia; Latagliata, Roberto; Sabattini, Elena; Riminucci, Mara; Godio, Laura; Catani, Lucia; Nicolosi, Maura; Perricone, Margherita; et al.
Abstract : Although infectious complications represent a relevant cause of morbidity and mortality in patients with myelofibrosis (MF), little is known about their incidence, outcome and risk factors. We retrospectively evaluated a cohort of 507 MF patients, diagnosed between 1980 and 2014 in five Italian hematology centers, to define the epidemiology of infections and describe the impact of ruxolitinib (RUX) treatment. Overall, 112 patients (22%) experienced 160 infectious events (grade 3–4, 45%) for an incidence rate of 3.9% per patient‐year. Infections were mainly bacterial (78%) and involving the respiratory tract (52% of cases). Also, viral (11%) and fungal infections (2%) were recorded. Overall, infections were fatal in 9% of the cases. Among baseline features, high/intermediate‐2 IPSS category (HR 1.8, 95%CI:1.2–2.7; P = 0.02) and spleen length ≥10 cm below left costal margin (HR 1.6, 95%CI:1.1–2.5; P = 0.04) were associated with higher infectious risk in multivariate analysis. Overall, the rate of infections was higher in the cohort of 128 RUX‐treated patients (44% vs. 20%, P < 0.001). In conclusion, IPSS‐category and splenomegaly, emerged as the main risk factors for infections in MF. RUX‐treated patients experienced significantly more infection episodes; however, future prospective studies are needed to isolate the confounding contribution of other risk factors such as disease stage. Am. J. Hematol. 92:37–41, 2017. © 2016 Wiley Periodicals, Inc.